Comparison of alternative media from organic waste as a growth media for the biological agent bacteria Pseudomonas spp - Erdiansyah, Iqbal; Viraneka, Rema (AGROMIX, 2024)
Introduction: Pseudomonas spp is one of the biological agents that has many abilities. With the high cost of synthetic media used as a medium for the propagation and growth of this bacteria, it is necessary to have alternative media that are cheap and environmentally friendly, one of which is by utilizing organic waste. This study aims to determine the comparison of the growth of Pseudomonas spp on alternative media from organic waste. Method: The design used was a non-factorial Completely Randomized Design (CRD) with 3 (three) treatments using types of bacteria propagation media, namely P0 = selective media formulation (Pseudomonas Isolation Agar), P1 = soybean water stew waste, and P2 = coconut water waste and repeated 6 times. Result: The results showed that the bacteria tested were Pseudomonas spp based on the Gram staining test and the pendar fluorescence test. The highest number of colonies on day 5 was found in coconut water media as well as the results of the absorbance test and the Pseudomonas spp had antagonistic properties against Xanthomonas sp. Conclusion: Alternative media from organic waste coconut water are the best media for the growth of Pseudomonas spp which have antagonistic properties against Xanthomonas sp.